Educational Robotics: reflections on an educators and teachers training in context - Torres, João Vítor; Rodrigues, Maria do Rosário; Grácio, João Carlos; Figueiredo, Miguel Ângelo (Aprender, 2023)
The article focuses on a continuous teacher training experience in the areas of computational thinking and robotics, which took place during the 2021/2022 school year, at a private school in the Greater Lisbon area. The training was requested by the school and was carried out by the authors of the article on the school premises. The teachers involved developed lesson plans, created some resources, and implemented them in the classroom, reflecting on their experience afterwards. These lesson plans and resources, as well as the reflections made by the teachers, were included in a digital publication. We used a case study methodology to determine if this training led to any changes in the practices of the teachers involved, by conducting a focus group, about a year after the training ended, as a privileged mean of data collection. The results indicate that the use of robotics in the school context, by the participants in the training, continued.